Road Safety Improvement on At-Grade Intersections - Abukauskas, Nemunas; Sivilevičius, Henrikas; Puodžiukas, Virgaudas; Lingytė, Ineta (The Baltic Journal of Road and Bridge Engineering, 2013)
Engineering improvement of roads is in many cases inseparable from the improvement of at-grade intersections, as one of the most hazardous engineering structures. At-grade intersections in Lithuania are currently subjected to intensive installation of different traffic engineering and safety measures. More and more often, to ensure road safety the measures of experimental nature are used the effect of which has not been specified yet. Therefore, for the research object three intersections were selected provided with safety islands with flexible plastic reflective posts. The research was carried out within the zone of conventional intersections with the left-turn deceleration and waiting lanes on the main roads of Lithuania. During the research the driving speeds were measured in three different locations and the changes in the speeds and in the frequency of traffic conflicts were determined. Using an analogical comparison of similar traffic engineering measures, a preliminary effect of the study measures was identified.